Loss-of-function genomic variants highlight potential therapeutic targets for cardiovascular disease - Jonas B. Nielsen (Nature Portfolio, 2020)
Drugs targeting cardiovascular disease (CVD) can have negative consequences for liver function. Here, the authors combine genome wide analyses on 69,479 individuals to identify loss-of-function variants with beneficial effects on CVD-related traits without negative impacts on liver function.